2015
DOI: 10.14393/bj-v31n1a2015-18200-
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidas inibidores da accase em plantas de Cenchrus echinatus em estresse hídrico

Abstract: RESUMO:Este projeto objetivou relacionar a eficiência de controle de herbicidas inibidores da ACCase aplicados em pós-emergência em plantas de Cenchrus echinatus submetidas a diferentes teores de água no solo. Os experimentos foram conduzidos em casa de vegetação, com a aplicação de três diferentes herbicidas (fluazifop-p-butil, haloxyfop-methyl e sethoxydim + óleo mineral Assist). O delineamento experimental utilizado para cada herbicida foi inteiramente casualizado, com 4 repetições, constituído de um fatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…However, on plants submitted to -0.07 MPa water management, there was no reduction, but a 30% mass increase, on average. These results are supported by a study conducted by Pereira et al (2015a), who observed that sethoxydim applied on southern sandbur plants caused a 90% dry mass reduction on plants kept with no water stress, in relation to the dry mass of plants with no herbicide application. These authors also affirm that the lowest dry masses obtained in plants under severe water stress are not related to the effect of the applied herbicides, but to the plants' morphological conditions, since they develop mechanisms of drought resistance, according to Taiz and Zeiger (2004).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…However, on plants submitted to -0.07 MPa water management, there was no reduction, but a 30% mass increase, on average. These results are supported by a study conducted by Pereira et al (2015a), who observed that sethoxydim applied on southern sandbur plants caused a 90% dry mass reduction on plants kept with no water stress, in relation to the dry mass of plants with no herbicide application. These authors also affirm that the lowest dry masses obtained in plants under severe water stress are not related to the effect of the applied herbicides, but to the plants' morphological conditions, since they develop mechanisms of drought resistance, according to Taiz and Zeiger (2004).…”
supporting
confidence: 77%
“…The application of sethoxydim was also not effective in applications on southern sandbur plants (Cenchrus echinatus) under water stress, reaching an average control of 66%, as reported by Pereira et al (2015a) and Klar et al (2015), regardless of the stage (4-6 leaves and 2-3 tillers). The Indian goosegrass species (Eleusine indica), when submitted to a high level of water stress, also had less herbicide effectiveness, as demonstrated in a study conducted by Pereira et al (2015b), as well as the morning glory species (Ipomoea grandifolia), who had its control damaged with the application of chlorimuron-ethyl and imazethapyr, when under water deficit conditions (Vitorino and Martins, 2012).…”
mentioning
confidence: 55%
“…The most frequent species, i.e., Adenocalymma sp., Cenchrus echinatus L. and Digitaria sp. are considered difficult to control (ARRUDA et al, 2015;PEREIRA et al, 2015).…”
Section: Experiment-1mentioning
confidence: 99%